MODEL FOREST CANOPY DENSITY PADA CITRA SPOT-6 UNTUK ESTIMASI POTENSI TEGAKAN POHON DI KAWASAN PENGELOLAAN HUTAN LINDUNG BATU SERAMPOK LAMPUNG SELATAN - Aulia Atmojo; Retno Triyani; Adam Irwansyah Fauzi; Muhammad Ulin Nuha; Meraty Ramadhini; Arif Rohman (Jurnal Fisika Unand, 2024)
Traditional forest inventory methods for obtaining tree stand data in the Batu Serampok Protected Forest Management Unit (KPHL) require significant time and resources. Therefore, remote sensing technology was employed to estimate the potential tree stand density. This study utilized the Forest Canopy Density (FCD) model and the Normalized Difference Vegetation Index (NDVI) from SPOT-6 satellite imagery to assess forest density. Field surveys were conducted to validate the image processing results. Statistical analysis, including correlation and linear regression tests, was performed. Forest density classes were converted into the number of trees per unit area using regression equations. Accuracy tests compared field data with estimated tree stand counts based on vegetation indices. The FCD correlation score was 0.85, higher than NDVI's 0.78, with linear regression results of 0.73 for FCD and 0.62 for NDVI. FCD demonstrated higher maximum accuracy (90.52%) compared to NDVI (84.08%), making it the preferred method for estimating tree stand potential. Overall, FCD reconstruction proved more accurate than NDVI, with the Batu Serampok KPHL predominantly characterized by moderate-density stands.